The Effect Of Liquidity Risk, Capital Buffer, And Income Diversification On Financial Stability Of Banks In Indonesia: Empirical Study on Conventional Commercial Banks Listed on the Indonesia Stock Exchange for the Period 2019-2023 - Nufus, Khayatun; Ruknan; Mahmudi, Chamdun; Amelinda, Iffahana Farah (Institut Bisnis dan Informatika Kesatuan, 2025)
Bank financial stability is one of the important aspects in maintaining economic health, given the vital role of banks as financial intermediaries. This study aims to analyze the effect of liquidity risk, capital buffer, and income diversification on bank financial stability. The unit of analysis in this study is conventional commercial banks listed on the Indonesia Stock Exchange during the period 2019-2023. The sampling technique used is purposive sampling, so that 20 conventional commercial banks were obtained. The data analysis technique used is panel data regression using Eviews 13 software. The results showed that, partially, liquidity risk, as measured by Liquidity Coverage Ratio (LCR) has a significant negative effect on bank financial stability, while Net Stable Funding Ratio (NSFR) has no significant effect on bank financial stability. Capital buffer has a significant positive effect on bank financial stability, while income diversification has a significant negative effect on bank financial stability. This study also shows that LCR, NSFR, capital buffer and income diversification simultaneously affect banks' financial stability. Keywords: Bank Financial Stability, Liquidity Risk, Capital Buffer, Income Diversification